Mesenchymal stem cells from the domestic ungulates: trends and outliers - Anna A Tvorogova; Anastasia V Kovaleva; Aleena A Saidova (International Journal of Veterinary Science and Research - Peertechz Publications, 2018)
Mesenchymal stem cells (MSCs) are a valuable source for regenerative therapy and tissue engineering. MSCs are multipotent adherent stem cells that can be isolated from different adult and fetal tissues. In contrast to human MSCs, MSCs from large animal models have not yet been described by the uniform criteria, which include the characteristic phenotype of surface molecules, expression of stemness markers and differentiation potencies. The current review describes state of the art for characterization for MSCs from three species of domestic ungulates, including cattle (Bos taurus), swine (Sus scrofa) and sheep (Ovis aries). The comparative analysis of surface phenotype, gene expression and differentiation capacities of MSCs from different origins allows defining the consensus phenotype of bovine, ovine and porcine MSCs. We also discuss the major data discrepancies and pitfalls that are complicating the successful research of MScs from domestic livestock. This review emphasizes the pressing need for the unification of mesenchymal stem cell criteria in the veterinary field.